A computationally efficient formulation of the governing equations for unit operation design. (November 2021) - Carranza-Abaid, Andres; Jakobsen, Jana P.
Highlights: A new formulation (PEF) of the governing equations for unit operation design. In average, the PEF can reduce the computation time by one order of magnitude. The Eulerian formulation and the PEF are mathematically equivalent. A PEF-based model of a gas-liquid contactor is validated with experimental data. Abstract: A computationally-efficient numerical method that uses a Pseudo-Eulerian formulation (PEF) for the design calculation of unit operations is presented and validated. This method is applicable to any unit operation that can be modelled using a system of ODEs. Performing the design of a unit operation in the PEF is tenfold faster than with the conventional Eulerian formulation (EF). The mathematical equivalence between the PEF and the EF is demonstrated by proving that the solution of different unit operation design problems provides the same numerical result independently of the formulation. It is shown that reducing the computation of the unit operation design problems also speeds the computation time of a process design or an optimization flowsheet. Additionally, as opposed to other computationally efficient methods for unit operation design, the PEF allows the accurate estimation of the concentration or temperature profiles of complex unit operations such as a multiphase multicomponent reactor system.